Identifikasi Potensi Bahaya Pada UKM Tahu dengan Metode Hazard Identification and Risk Assessment Sebagai Langkah Penerapan Manajemen K3 - Achmad Samudera Dewantara; Nia Sastra Permata; Sherin Ramadhania (Jurnal Serambi Engineering, 2025)
The implementation of Occupational Health and Safety (OHS) management reflects a business owner's commitment to protecting workers' health and safety. One key step in implementing OHS is identifying and mapping potential workplace hazards. In small and medium enterprises (SMEs) producing tofu, such hazards often arise during the production process. The HIRA (Hazard Identification and Risk Assessment) method is used for hazard mapping because it systematically identifies hazard locations and critically analyzes risk levels. This study was conducted at a tofu SME in Krajan, Surakarta, and identified several potential hazards categorized into four groups: hazards from the work environment, production materials, unsafe equipment, and production waste. The analysis revealed five high-risk hazards and four moderate-risk hazards. Through hazard mapping, business owners are expected to take preventive measures to minimize or eliminate exposure to these risks. This ensures worker health and safety while maintaining a smooth and uninterrupted production process.